Challenges in diagnosing and treating Liddle syndrome in resource-limited settings: A case report from Indonesia - Prabowo, Nurhasan A.; Putranto, Wachid; Myrtha, Risalina; Ardyanto, Tonang D.; Gautama, Coana S.; Wulandari, Evi L.; Hermawati, Berty D.; Putri, Desy P.; Ramadhani, Artika; Dewi, Herlina K. (Narra Sains Indonesia, 2024)
Liddle syndrome, a rare form of monogenic hypertension, poses significant diagnostic and therapeutic challenges due to its phenotypic variability and the need for genetic testing. The rarity of the condition, coupled with the limited availability of first-line treatments such as epithelial sodium channel (ENaC) blockers, makes this case report particularly urgent and novel, highlighting alternative management strategies in resource-limited settings. The aim of this case report was to present the diagnostic challenges, therapeutic strategies, and clinical outcomes of a patient with Liddle syndrome who did not have access to ENaC blockers, emphasizing the importance of early recognition and personalized treatment. A 35-year-old female presented with resistant hypertension (190/100 mmHg) and bilateral limb weakness. Laboratory results revealed persistent hypokalemia, hypernatremia, and metabolic alkalosis. Low aldosterone levels, alongside clinical and family history, led to the diagnosis of Liddle syndrome. Genetic testing was not conducted due to resource limitations, and ENaC blockers were unavailable. The patients were managed with a combination of alternative antihypertensive agents, potassium supplementation, and a low-sodium diet. Although this approach led to modest improvements in blood pressure and motor strength, persistent hypokalemia and hypernatremia underscored the suboptimal control of the syndrome's underlying pathophysiology in the absence of ENaC blockers. This case highlights the challenges faced in resource-limited settings and the need for innovative strategies to manage rare conditions like Liddle syndrome. Liddle syndrome's diagnostic and therapeutic challenges underscore the critical importance of early recognition and access to targeted therapies. In the absence of ENaC blockers, alternative treatment strategies can provide some benefit, but they often fall short of optimal management. This case emphasizes the need for enhanced clinical awareness, improved access to genetic testing, and the development of personalized treatment approaches to achieve better patient outcomes.